The Effect of Employment And Marriage on The Level of Community Welfare (Studies in Health Sector) in Indonesia - Ranivita Ika Prasetiyaningtyas; Rochmat Aldy Purnomo; Sayid Abas; Choirul Hamidah; Yeni Cahyono (MediaTrend, 2022)
This study aims to determine the effect of household health level on the level ofwelfare in Indonesia. Health is a human right and one of the elements of welfare that must be realized in accordance with the ideals of the Indonesian nation referred to in Pancasila and the 1945 Constitution of the Republic of Indonesia. Health is an indicator of welfare for the community, so that every community has the right to obtain health services good and quality. The level of welfare is one of the achievements of the Sustainable Development Goals (SDGs). The problem that forms the basis of this research is to find out how much influence labor and marriage have on the level of social welfare, especially in the health sector in Indonesia. The research method used is a quantitative method with a linear regression model using secondary data. To find out the variables that influence the level of household health on the level of welfare in Indonesia, the variables used are marital status and the employment sector. To explain the level of household welfare, a cross-tabulation analysis was carried out. Meanwhile, to examine the relationship between the dependent variable and the independent variable, linear regression analysis was used. The research results obtained that the level of welfare in the health sector is influenced by employment variables and marriage variables. So it can be concluded that people who have jobs and are married have a much better level of welfare in the health sector. The hope is that all people in Indonesia are expected to obtain quality health facilities so that their level of welfare increases. Health improvement can be done by increasing medical facilities and improving the quality of medical staff